Northwest Africa 8694, a ferroan chassignite: Bridging the gap between nakhlites and chassignites. (1st August 2020) - Hewins, R.H.; Humayun, M.; Barrat, J.-A.; Zanda, B.; Lorand, J.-P.; Pont, S.; Assayag, N.; Cartigny, P.; Yang, S.; Sautter, V.
Abstract: The origin(s) of the chassignites and nakhlites, closely related martian olivine and augite cumulates, respectively, are much debated. Northwest Africa (NWA) 8694 is the third chassignite to be discovered and the most ferroan, containing 85% olivine (Fo54 ). Its O-isotope compositions (δ 18 O ∼ 4.4‰, Δ 17 O ∼ 0.30‰) are typical of other martian meteorites. It has adcumulate texture and contains cumulus chromite, poikilitic pigeonite (En56 Fs37 Wo7 ) and mesostasis (trapped interstitial liquid). The latter contains pyroxene and plagioclase (An23 Ab70 Or8 ) plus rare K- feldspar (Or74 ), and has a trachyandesitic to trachytic bulk composition. Melt inclusions in olivine contain a variety of phases including biotite and rare amphibole. Olivine, chromite, and pigeonite compositions are intermediate between those of the other chassignites and those of the nakhlites. Augite, which appears to mantle pigeonite, has a composition overlapping that in nakhlite NWA 998 and some other nakhlites at (En41-40 Wo38-39 ). The augite lamellae in pigeonite 1–2 μm in apparent width, and the survival of Ca zoning in olivine, suggest a near-surface cooling environment. The bulk-rock REE concentrations in the three chassignites do not correlate with Mg# but depend on the abundance of trapped liquid. The form of REE patterns calculated for olivine subtraction is very like those of nakhlite mesostases, but the observed concentrations of LREE in NWA 8694 trapped liquid have a very steep slope. This is explained by undersampling of baddeleyite and zirconolite that occur near olivine contacts with mesostasis. Though pyroxene is unzoned, its trace element variations indicate fractional crystallization. The range of olivine compositions in the three chassignites (Fo79-54 ) is too large to result from the crystallization sequential growth of olivine from a single magma undergoing fractional crystallization. The Ge/Si ratios show degassing of NWA 8694 which sets this chassignite apart from other chassignites and nakhlites, implying a unique batch of magma for its genesis. Many potential parent liquids are capable of generating the NWA 8694 olivine composition, though not its alkaline mesostasis. We calculated that Nakhla parent liquid NA01a (Stockstill et al., 2005) with 10% Nakhla core olivine added would produce both olivine crystals and alkaline daughter liquids with compositions matching those of NWA 8694. This meteorite is a chassignite cumulate containing nakhlitic mesostasis, a direct link between the chassignites and the nakhlites and the association of dunitic to trachytic compositions is reminiscent of terrestrial shield volcanoes. Chassignites and nakhlites were possibly formed when solidification fronts on chamber walls were disrupted, mainly as side eruptions of olivine-charged magmas from the deeper zones, and augite-charged fractionated magmas from nearer the summit of a volcano resembling Piton de la Fournaise on Earth.